IMPROVING PRESCHOOL TEACHERS’ DRAWING SKILLS THROUGH CREATION EARLY CHILDHOOD BOOKS STORY TRAINING - Yanuarsari, Revita; Muchtar, Hendi (PEOPLE: International Journal of Social Sciences, 2017)
This research is expected to solve the lack of preschool teachers’ drawing skill. It is conducted by giving creation early childhood books story training. This helps preschool teachers to master basic drawing techniques. The research uses qualitative approach. There are 3 (three) stages in this research namely Pre, On Going and Post Training. The used instruments are observation and questionnaire. With this training, it is expected that early childhood teachers can create a story for Early Childhood, illustrate the story to draw, demonstrate and animate the fairy tale, so that learning in early childhood will be more effective, especially the character learning with story or fairy tales.